Accelerated midlife endocrine and bioenergetic brain aging in APOE4 females - Wang, Tian; Mao, Zisu; Shang, Yuan; Merlini, Simona; Vitali, Francesca; Wiegand, Jean-Paul; Brinton, Roberta Diaz (Frontiers in Aging Neuroscience, 2025)
Female sex, age, and APOE4 genotype are the greatest risk factors for Alzheimer′s disease. Using a translational perimenopause mouse model based on human Stages of Reproductive Aging Works (STRAW) criteria, we investigated the impact of APOE genotype on female midlife endocrine aging, peripheral metabolic indicators, brain bioenergetic pathways, mitochondrial function, neuroimmune activation, and myelination. Compared to APOE3 females, APOE4 females exhibited accelerated endocrine aging that was coincident with failure to mount adaptive bioenergetic reprogramming and significant decline in mitochondrial function that were coupled with increased immune activation and demyelination in brain. In women, APOE4 was associated with early menopause. Further, APOE4 women experiencing early menopause exhibited the highest risk of Alzheimer′s. These results provide plausible mechanistic pathways underlying the earlier emergence and greater risk of Alzheimer′s in APOE4 postmenopausal females. Collectively, these findings support midlife as a critical window for intervention to prevent or delay the onset of the prodromal stage of Alzheimer′s disease in APOE4 carriers.